Sejarah Perkembangan Tasawuf - Zuherni AB (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
The Prophet is the model of spirit for the world. His God-consciousness, deep spiritualism, acts of worship, and love for Allah are preserved and propagated by an Islamic science called Tasawwuf (Sufism). The esoteric teachings of Tasawwuf (Sufism) which purification of the heart are transmitted from Muhammad to those who had the capacity to acquire the direct experiential gnosis of God, which is passed on from teacher to student through the centuries. Different devotional styles and traditions developed over the time, reflected the perspectives of different masters and the accumulated cultural wisdom of the orders. Typically all of these concern themselves with the understanding of subtle knowledge and education of the heart to purify it and to find the love of God.